Math

posted by .

Find the value(s) of x, so that f’(x) = 0 for the function f(x) = 4x3 – 6x2 – 24x.

• Math -

I will assume you meant
f(x) = 4x^3 – 6x^2 – 24x

then
f'(x) = 12x^2-12x - 24
= 0
divide by 12
x^2 - x - 2 = 0
(x-2)(x+1) = 0
x = 2 or x = -1

Similar Questions

1. math a2

the expression 4x3-6x2 represents the area of a triangle. write the expression as the product of two factors. 4x3-6x2 as in: FOURx 3(power) -(minus) SIXx 2(power)
2. math a2

the expression 4x3-6x2 represents the area of a triangle. write the expression as the product of two factors. 4x3-6x2 as in: FOURx 3(power) -(minus) SIXx 2(power)
3. math a2

the expression 4x3-6x2 represents the area of a triangle. write the expression as the product of two factors. 4x3-6x2 as in: FOURx 3(power) -(minus) SIXx 2(power)
4. math a2

the expression 4x3-6x2 represents the area of a triangle. write the expression as the product of two factors. 4x3-6x2 as in: FOURx 3(power) -(minus) SIXx 2(power)
5. algebra

Did I do this problem the correct way if so is there a shorter way to explain this?
6. math

Use polynomial long division to divide -4x3 + 24x2 – 24x + 4 by x2 – 5x + 1